Enabling factors for financing and implementing postdisaster operations - Junko Mochizuki; Joshua Hallwright; John W. Handmer (Asian Development Bank (ADB), 2019)
As the economic costs of disasters increase in Asia, recent years have seen wide adoption of policy instruments to support disaster resilience. Many of these instruments - such as sovereign insurance, contingency credit, reserve funds, and forecast-based financing - are designed to provide predictable access to finance in case of catastrophic disasters. Yet providing timely access is only one of the many issues that must be addressed for the complex postdisaster operation to function. Reviewing recent experiences - such as the 2015 earthquake in Nepal, the 2015 Cyclone Pam in Vanuatu, and the 2010 flood in Pakistan - this study first describes the governance complexity commonly seen in the postdisaster contexts, complexities such as the acute inflow of new actors and competing operational objectives. We then identify the potential opportunities, as well as the limitations, of existing financing arrangements in facilitating disaster resilience. In conclusion, we outline five recommendations to building enabling environments.
Keywords: Q54; 330; disaster resilience; disaster risk finance; governance